HDPE Recycled Plastic Composite with Cellulose Fiber Filler Based on Oil Palm Empty Fruit Bunches - Wawan Atmaja; Zulnazri Zulnazri; Agam Muarif; Willy W (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Composite is an advanced material product that has better mechanical properties than a single material and has high tensile strength; it can be applied to the construction of boat walls, car dashboards, electronic casings, and others. This study examines the composite quality of HDPE recycled plastic using cellulose fiber-based on Empty Palm Oil Bunches (TKKS), which is processed through an extruder and injection melt blending system. The method used is mixing plastic and fiber materials with a roll mill and blending with an extruder. Cellulose fiber was dissolved with compatibilizer maleic anhydrous (MAH) 2.5% as much as 20 mL, stirred until smooth, and HDPE plastic was dissolved with benzoyl peroxide (BPO) 0.5% 10 mL. The composite was molded with hot pores at 160-170 ᴼC. The tensile test shows the strength of HDPE composite (90: 10) is 27.0 Mpa with maximum load reaching 274 N, HDPE composite (80: 20) is 26.0 MPa with full load 258 N, HDPE composite (70: 30) is 320.0 MPa with a maximum load of 316 N. SEM shows the surface structure of the fiber-compatible HDPE composite. Functional group analysis showed that HDPE composites had O-H and C-O-C functional groups derived from lignocellulosic OPEFB material. The appearance of these two peaks indicates a compatible interaction between the HDPE matrix and cellulose. DSC shows that HDPE composites have a degradation temperature of up to 260 ᴼC and a decomposition temperature of 493.45 ᴼC. This temperature indicates that the HDPE-cellulose composite can withstand heat until it decomposes at a temperature of 493 45 oC.